Mibefradil and Flunarizine, Two T-Type Calcium Channel Inhibitors, Protect Mice against Lipopolysaccharide-Induced Acute Lung Injury. (10th November 2020) - Wan, Limei; Wu, Weibin; Jiang, Shunjun; Wan, Shanhe; Meng, Dongmei; Wang, Zhipeng; Zhang, Jiajie; Wei, Li; Yu, Pengjiu
Abstract : Recent studies have illuminated that blocking Ca 2+ influx into effector cells is an attractive therapeutic strategy for lung injury. We hypothesize that T-type calcium channel may be a potential therapeutic target for acute lung injury (ALI). In this study, the pharmacological activity of mibefradil (a classical T-type calcium channel inhibitor) was assessed in a mouse model of lipopolysaccharide- (LPS-) induced ALI. In LPS challenged mice, mibefradil (20 and 40 mg/kg) dramatically decreased the total cell number, as well as the productions of TNF- α and IL-6 in bronchoalveolar lavage fluid (BALF). Mibefradil also suppressed total protein concentration in BALF, attenuated Evans blue extravasation, MPO activity, and NF- κ B activation in lung tissue. Furthermore, flunarizine, a widely prescripted antimigraine agent with potent inhibition on T-type channel, was also found to protect mice against lung injury. These data demonstrated that T-type calcium channel inhibitors may be beneficial for treating acute lung injury. The important role of T-type calcium channel in the acute lung injury is encouraged to be further investigated.